2019
DOI: 10.1172/jci127125
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing miR-21 activity in tumor-associated macrophages promotes an antitumor immune response

Abstract: microRNA-21 (miR-21) is the most commonly upregulated miRNA in solid tumors. This cancer-associated microRNA (oncomiR) regulates various downstream effectors associated with tumor pathogenesis during all stages of carcinogenesis. In this study, we analyzed the function of miR-21 in noncancer cells of the tumor microenvironment to further evaluate its contribution to tumor progression. We report that the expression of miR-21 in cells of the tumor immune infiltrate, and in particular in macrophages, was responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 76 publications
(114 reference statements)
4
90
0
Order By: Relevance
“…These ndings correlate with our previous studies showing a speci c uptake of pHLIP in tumor associated macrophages. 23 Similar to the results observed in vivo, acidi cation of the media (pH = 6.2) promoted a marked increase of A546-Var3 uptake in mouse macrophages compared to macrophages cultured at a neutral pH ( Fig. 2a).…”
Section: Mainsupporting
confidence: 85%
“…These ndings correlate with our previous studies showing a speci c uptake of pHLIP in tumor associated macrophages. 23 Similar to the results observed in vivo, acidi cation of the media (pH = 6.2) promoted a marked increase of A546-Var3 uptake in mouse macrophages compared to macrophages cultured at a neutral pH ( Fig. 2a).…”
Section: Mainsupporting
confidence: 85%
“…There is no common scientific consensus about the exact mechanism of miR-21 in the induction or repression of the inflammatory program. Several manuscripts suggest miR-21 as an anti-inflammatory target (41,(73)(74)(75), while others suggested this miRNA as a crucial proinflammatory factor (36,40,76). We observed an overall decrease in IL6 and IL1b and an increase in IL10 abundance in septic miR21∆myel when compared to septic WT mice.…”
Section: Discussionmentioning
confidence: 45%
“…MiRNAs have been confirmed to play important roles in the occurrence of EC. [19][20][21] In this research, we found that the downregulation of miR-7-5p could notably suppress the growth of EC cells. Our study firstly explored the role of miR-7-5p in EC.…”
Section: Discussionmentioning
confidence: 57%